The effects of minimum quantity lubrication parameters on the lubrication efficiency in the turning of plastic mold steel - Hamdi, Amine; Yapan, Yusuf Furkan; Uysal, Alper; Merghache, Sidi Mohammed (SPRINGER LONDON LTD, 2024)
This study aims to investigate the impact of parameters associated with minimum quantity lubrication (MQL) in CNC turning of DIN 1.2738 plastic mold steel. The independent parameters considered include flow rate (Fr\documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$${F}_{r}$$\end{document}), nozzle distance (Nd\documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$${N}_{d}$$\end{document}), and nozzle angle (Na\documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$${N}_{a}$$\end{document}), with the objective of ensuring effective lubrication. The study focuses on evaluating surface roughness, cutting temperature, and specific cutting energy (SCE) to assess machinability. Experiments were conducted using coated carbide inserts SNMG 120,412-km and a commercially available vegetable oil-based cutting fluid, Eraoil KT/2000. Constant cutting parameters, such as cutting speed (220 m/min), feed rate (0.05 mm/rev), depth of cut (0.5 mm), nose radius (1.2 mm), working pressure (0.5 MPa), and nozzle radius (1 mm), were maintained. The methodology employed various analytical approaches, including analysis of variance (ANOVA), response surface methodology (RSM), gray relational analysis (GRA), and desirability function (DF). The results indicate that the MQL system effectively provided lubrication over a short nozzle distance of 10 mm by employing a high flow rate of 51 ml/h and a significant nozzle angle of 60 degrees. These conditions resulted in satisfactory performance for machinability-related parameters. Consequently, surface roughness (Ra\documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$${R}_{a}$$\end{document}) remained between 0.15 and 0.18 mu m, cutting temperature (Tc\documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$${T}_{c}$$\end{document}) ranged from 130 to 135 degrees C, and SCE consumption (Ecs\documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$${E}_{cs}$$\end{document}) was reduced to 3.37 J/mm3.
Keywords: MQL; Flow rate; Nozzle distance; Nozzle angle; DIN 1.2738 steel; CNC turning; CUTTING FLUIDS; VEGETABLE-OIL; OPTIMIZATION; ENERGY; ALLOY; Automation & Control Systems; Engineering